Badanie rynku ubezpieczeń III filara z zastosowaniem analizy korespondencji - Batóg, Barbara; Mojsiewicz, Magdalena; Wawrzyniak, Katarzyna (The Examination of the Third Kind of Insurance Market with the Use of the Correspondence Analysis, 2009)
In the paper, the authors undertook an attempt to describe the third kind of insurance market with the use of the multidimensional correspondence analysis. A main objective of the research was the answer on the question in which degree preferences of respondents concerning this type of insurances depend on such variables as: sex, age, civil status, level of education, place of living, occupation, and number of children. The analysis concerned also the answers on the questions about the motives for purchasing insurance products of the third kind and motives for the choice of insurance firm. (original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 47, s. 149-156